Spectrum and Frequency of Germline FANCM Protein-Truncating Variants in 44,803 European Female Breast Cancer Cases - Figlioli, Gisella; Billaud, Amandine; Wang, Qin; Bolla, Manjeet K.; Dennis, Joe; Lush, Michael; Kvist, Anders; Adank, Muriel A.; Ahearn, Thomas U.; Antonenkova, Natalia N.; Auvinen, Päivi; Behrens, Sabine; et al. (Cancers, 2023)
FANCM germline protein truncating variants (PTVs) are moderate-risk factors for ER-negative breast cancer. We previously described the spectrum of FANCM PTVs in 114 European breast cancer cases. In the present, larger cohort, we report the spectrum and frequency of four common and 62 rare FANCM PTVs found in 274 carriers detected among 44,803 breast cancer cases. We confirmed that p.Gln1701* was the most common PTV in Northern Europe with lower frequencies in Southern Europe. In contrast, p.Gly1906Alafs*12 was the most common PTV in Southern Europe with decreasing frequencies in Central and Northern Europe. We verified that p.Arg658* was prevalent in Central Europe and had highest frequencies in Eastern Europe. We also confirmed that the fourth most common PTV, p.Gln498Thrfs*7, might be a founder variant from Lithuania. Based on the frequency distribution of the carriers of rare PTVs, we showed that the FANCM PTVs spectra in Southwestern and Central Europe were much more heterogeneous than those from Northeastern Europe. These findings will inform the development of more efficient FANCM genetic testing strategies for breast cancer cases from specific European populations.
CRIS-Team Scopus Importer:2023-07-28
Keywords: breast cancer predisposition; breast cancer risk factors; FANCM PTVs spectrum; protein truncating variants; PTVs